UPAYA PENINGKATAN HASIL BELAJAR BAHASA INDONESIADENGAN MENGGUNAKAN METODE PEMBELAJARAN GENERATIFSISWA KELAS VA SDN 004 BAGAN BESAR KECAMATAN BUKIT KAPUR - Ratna Situmeang (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This study aims to improve the Indonesian language learning outcomes of fifth-grade students at SDN 004 Bagan Besar through the use of generative teaching methods. The subjects in this study were fifth-grade students of SDN 004 Bagan Besar in the Indonesian language subject, specifically on the material of commenting on factual issues. This research is a form of classroom action research, which is a practical approach aimed at improving deficiencies found in classroom learning, including enhancing students’ creativity and their ability to generalize concepts. This is carried out through specific actions designed to improve teaching practices so that learning becomes more effective and professional. Based on the observations conducted, student learning outcomes improved significantly. This improvement can be seen from the first meeting before the implementation of the generative teaching method, where learning outcomes in the first cycle reached 76%, and increased further in the second cycle to 92%. Based on this analysis, it can be concluded that the application of generative teaching methods can improve the learning outcomes of fifth-grade students at SDN 004 Bagan Besar, Kecamatan Bukit Kapur.